A data-driven analysis of the mediating role of physical fitness in the relationship between motivation and physical educational learning outcomes - M. Dina Sefrianda; Nurul Ihsan; Masrun; Sepriadi; Ardo Okilanda (CV. FOUNDAE, 2026)
Background: Learning outcomes in physical education are influenced by both psychological and physiological factors. However, the mechanism through which motivation contributes to learning outcomes, particularly through physical fitness as an intervening variable, remains underexplored in educational research. Aims: This study aims to analyze the direct and indirect effects of motivation and physical fitness on physical education learning outcomes among junior high school students. Method: A quantitative, data-driven approach with a causal-associative design was employed. The sample consisted of 32 students selected using purposive sampling. Data were collected through a Likert-scale motivation questionnaire, the Indonesian Student Fitness Test (TKSI Phase D), and students’ academic performance records. Data analysis included descriptive statistics, normality testing, and mediation analysis using multiple regression. Results: The results indicate that motivation significantly affects physical fitness (β = 0.547, p < 0.001) and has a direct effect on learning outcomes (β = 0.295, p < 0.05). Physical fitness also significantly influences learning outcomes (β = 0.331, p < 0.05). Furthermore, physical fitness partially mediates the relationship between motivation and learning outcomes, with an indirect effect of 27.6%. Conclusion: Motivation and physical fitness significantly influence physical education learning outcomes, both directly and indirectly. Physical fitness functions as an important mediating variable, highlighting the need for integrated strategies that enhance both student motivation and physical condition to improve academic performance.